(untitled) (Bangladesh Journal of Plant Breeding and Genetics, 2011)
An attempt was made to study genotypic variance, phenotypic variance, environmental variance, genotypic coefficient of variation (GCV), phenotypic coefficient of variation (PCV), heritability (h2b) and genetic advance (GA) for some rice genotypes during July 2007 to January 2009 at BSMRAU campus, Gazipur 1706. Significant variations were obtained among the genotypes for all the characters studied. Considering genetic parameters high genotypic coefficient of variation (GCV) value was observed for harvest index followed by yield per hill, number of tillers per hill, number of filled grain per panicle, whereas days to maturity showed very low GCV. High heritability with high genetic advance (GA) observed for yield per hill followed by number of tillers per hill, number of filled grains per panicle indicated that these characters were under additive gene control and selection for genetic improvement for these traits might be effective. DOI: http://dx.doi.org/10.3329/bjpbg.v24i2.17004